COVID-19 w Polsce — sekwencja epidemii według modelu SIR - Pastuszka, Katarzyna; Pastuszka, Sławomir (Wydawnictwo Uniwersytetu Wrocławskiego, 2021)
The paper aims to indicate the duration and intensity of the COVID-19 epidemic in Poland. Toa chieve this goal, the SIR interval model was used. The study was based on data from the Central Statistical Office, Hopkins University, and the Institute of Global Health at the University of Geneva. Based on the analysis results, it was established that the prognosis of the epidemic’s course largely depends on the size of the adopted R virus reproduction coefficient. The higher the coefficient,the more rapid the predicted course of the epidemic, the shorter the duration, and the greater the number of infected. And vice versa: the smaller the coefficient, the milder its course, the longer its duration, and the smaller the number of infected. For this reason, it is important to accurately assess the intensity of the epidemic’s development measured by the virus renewal rate, depending on the nature and intensity of interpersonal contacts. Perhaps in a given country different values of the coefficient for urbanized and rural areas should be used.
Keywords: SARS-CoV-2 virus; SIR epidemiological model; prognosing